MAPPING INDIA-NIGERIA RELATIONS: BRINGING ENERGY SECTOR INTO FOCUS - Awungshi, Yaruingam; Khashimwo, Pamreihor (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
India and Nigeria, two populous nations with rapidly growing economies, have cultivated a multifaceted relationship that extends beyond diplomatic ties. This paper delves into the intricate web of India-Nigeria relations, with a specific emphasis on the pivotal role of the energy sector. The energy sector has emerged as a linchpin in this bilateral relationship, showcasing the dynamics of energy diplomacy between the two nations. Nigeria, an African energy giant, holds abundant reserves of oil and gas, while India, one of the world’s fastestgrowing energy consumers, presents a compelling market for Nigerian energy resources. This paper scrutinises the evolution of this partnership, tracing its historical roots to the present day. Furthermore, it explores the geopolitical dimensions that shape energy cooperation, including Nigeria’s position as a vital oil supplier to India, and the diplomatic efforts taken to ensure a stable energy supply. The study also addresses the challenges and opportunities inherent in this energy-centric partnership, from market access issues to the potential for technology and knowledge transfer. By shedding light on the nuances of India-Nigeria relations within the energy sector, this research contributes to a deeper understanding of the global energy landscape and the strategic interests that underpin the ties between emerging economies.